Fabrication and characteristics of Zn1–xSnxO nanorod/ITO composite photocatalytic films. (27th April 2020) - Dung T., Nguyen; Dang Tran, Chien; Trinh Duc, Thien; Duong, Anh Tuan; Pham Duc, Thang; Nguyen Nang, Dinh; Nguyen, Dinh Lam
Abstract: Zn1−x Snx O NRs/ITO composite photocatalytic films were fabricated by the hydrothermal method. A concentration of Sn dopant in Zn1−x Snx O nanorods (NRs) was varied from 0% to 7%. The structural and surface morphology characteristics of Zn1−x Snx O NRs/ITO composite photocatalytic films were investigated by X-Ray diffraction (XRD) and scanning electron microscopy (SEM), respectively. In addition, photocatalytic properties of synthesized materials were evaluated by degradation rates of Rhodamine-B aqueous solutions under UV light irradiation. The SEM results indicated that, with an increasing concentration of Sn dopant in Zn1−x Snx O NRs/ITO, the effective surface areas were declined by an exponential decay function and the reduction was negligible as the Sn doping concentration was higher than 3%. With the similarity in effective surface area, the contribution of Sn in the enhancement of the photocatalytic activity of Zn0.93 Sn0.07 O NRs/ITO is clearly observed with 41% improvement in comparison to ZnO NRs/ITO.